2018
DOI: 10.18689/ijbr-1000105
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Area under the Curves for Insulin Secretion in Diabetes

Abstract: BackgroundConcerning diabetic nutritional therapy, Calorie Restriction (CR) and Low Carbohydrate Diet (LCD) have been on discussion. Authors continue clinical research related to CR, LCD, Morbus(M) value and insulin secretion. Subjects and MethodsSubjects were 42 patients (63.4 years on average) with type 2 diabetes mellitus (T2DM) with its immunoreactive insulin (IRI) =<5μU/mL. Methods included CR breakfast with carbohydrate 70g (Carbo70), Insulinogenic Index (IGI) calculation and daily profile of blood gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Therefore, we analyzed AUC and ⊿AUC for glucose and IRI during 0-2h and analyzed several related data [23]. The result showed that the obtained distribution of M value was wider than the distribution of mean blood glucose, and then the difference can be clearly grasped [24]. In this way, even if the levels of HbA1c and mean blood glucose are nearly the same in many diabetic cases, the M value level could be clinically useful for detecting unstable glucose variability such as larger MAGE [17].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Therefore, we analyzed AUC and ⊿AUC for glucose and IRI during 0-2h and analyzed several related data [23]. The result showed that the obtained distribution of M value was wider than the distribution of mean blood glucose, and then the difference can be clearly grasped [24]. In this way, even if the levels of HbA1c and mean blood glucose are nearly the same in many diabetic cases, the M value level could be clinically useful for detecting unstable glucose variability such as larger MAGE [17].…”
Section: Discussionmentioning
confidence: 98%
“…The result showed the intersection of case D and case F (Fig- 3b), where the relative difference seemed to exist between the total area of IGI and the area of ⊿IGI. In previous studies, elder patients tended to show slower glucose and IRI responses with higher IRI values and glucose 2 hours after a meal [24]. Therefore, we analyzed AUC and ⊿AUC for glucose and IRI during 0-2h and analyzed several related data [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously investigated AUC for insulin secretion in diabetes [30]. Carbo70 loading was performed on 42 cases of T2DM, and the insulin response was examined in 0 to 30 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…Our group investigators have clarified the physiological beneficial role from hyperketonemia in the axis of a pregnant mother, newborn, placenta and fetus [12]. Furthermore, a comparison of the daily profile of glucose variability on CR and LCD has investigated, and CR breakfast with 70g of carbohydrate has been utilized for meal tolerance test (MTT) similar to 75gOGTT [13,14].…”
Section: Introductionmentioning
confidence: 99%